Changes in the Order of Family Life Events in 20th-Century Europe: A Cross-Regional Perspective - Reto Burgin; Reto Schumacher; Gilbert Ritschard (Historical Life Course Studies)
This article analyzes the evolution of the sequencing of family life events in Europe during the second half of the 20th century using individual data from the European Social Survey and from the Generation and Gender Program. Considering the four events ‘leaving the parental home‘, ‘first cohabiting union‘, ‘first marriage‘, and ‘first parenthood‘, we hypothesize a transition from a traditional standard event order characterized by a high degree of synchronization between the first three events towards a new standard whose features are a high degree of de-synchronization between first cohabitation and first marriage and a reversal of the traditional order between first marriage and first parenthood. We also hypothesize cross-regional differences in the timing and in the shape of the transition from one standard to another. Applying specifically developed tools to visualize and analyze event sequences, we show important regional variation in the evolution of the sequencing of family life events. Hardly any change can be observed in Southern Europe, where the sequencing behavior of family events has remained highly standardized and rooted in the traditional standard. In Eastern Europe where family event sequences have become less standardized and where a particular sequence characterized by the reversal of the traditional order between leaving home and family formation has been observed, the hypothesized transition is still in its very beginning. In Western Europe the transition is clearly on its way, but no re-standardization towards a new standard can be observed as for now. As expected, the transition is most advanced in Northern Europe, where evidence for a certain re-standardization process in the sequencing of family life events has been found.